LOVETT Scaling with Flex Sensor and MYO Armband for Monitoring Finger Muscles Therapy of Post-Stroke People - Alfian Hidayat, Achmad; Arief, Zainal; Happyanto, Dedid Cahya (Politeknik Elektronika Negeri Surabaya (PENS), 2015)
LOVETT scale is a common parameter used by the doctor or therapist to determine the muscle strength of the patientâs hands, especially patients with post-stroke. As a result of previous work of our group, a sensory glove for monitoring finger muscle therapy for post-stroke people with the name of Electronic Therapy Gloves (ETG) was proposed. With the flex sensor that embedded to the gloves we can measure the LOVETT scale of the post-stroke people. This sensory glove can help the patient doing their rehabilitation fast so that they donât have to go to the hospital every week to check up their progress. In this work, we combine the data of sensory glove and the MYO armband for LOVETT scaling that has never been done before. The output of the Electronic Therapy Gloves can be optimized by 25%. All the LOVETT grade can be identify by the gloves, then it can help the doctor monitor the patientâs rehabilitation just by looking the patientâs record data with ETG.Keyword: LOVETT scale, flex sensor, MYO armband, post-stroke, rehabilitation.